Institutional Barriers and Bridges for Climate Proofing Waterway Infrastructures. (January 2019) - Willems, Jannes J.; Busscher, Tim
Although the urgency for climate proofing waterway assets grows, to date, little is known about the organizational learning process of infrastructure operators to address this urgency. Climate proofing infrastructure increasingly requires infrastructure operators to rethink the original aims of their networks (such as bringing prosperity by enabling transportation), which relates to the notion of double-loop learning. The goal of this article is to identify institutional barriers and bridges that condition learning processes of infrastructure operators in climate proofing waterway infrastructures. This article is based on a case study of the Dutch national inland waterway network. Our findings suggest that climate proofing infrastructure requires an integrative and inclusive approach, in which the focus on waterway assets is loosened and infrastructure operators become more oriented towards wider, larger regional developments. However, the barriers and bridges encountered in the case study suggest that the Dutch waterway operator Rijkswaterstaat mainly focuses on refining and optimizing the current waterway network, i.e., single-loop learning. The questioning of underlying values, i.e., double-loop learning, is more complicated and has to be actively organized.